Antiviral activity, safety, and pharmacokinetics/pharmacodynamics of tenofovir alafenamide as 10-day monotherapy in HIV-1-positive adults - Ruane, Peter J; DeJesus, Edwin; Berger, Daniel; Markowitz, Martin; Bredeek, U Fritz; Callebaut, Christian; Zhong, Lijie; Ramanathan, Srini; Rhee, Martin S; Fordyce, Marshall W; Yale, Kitty (Journal of acquired immune deficiency syndromes (1999), 2013)
To evaluate the antiviral activity, safety, pharmacokinetics, and pharmacokinetics/pharmacodynamics of short-term monotherapy with tenofovir alafenamide (TAF), a next-generation tenofovir (TFV) prodrug. A phase 1b, randomized, partially blinded, active- and placebo-controlled, dose-ranging study. Treatment-naive and experienced HIV-1-positive adults currently off antiretroviral therapy were randomized to receive 8, 25, or 40 mg TAF, 300 mg tenofovir disoproxil fumarate (TDF), or placebo, each once daily for 10 days. Thirty-eight subjects were enrolled. Baseline characteristics were similar across dose groups. Significant reductions in plasma HIV-1 RNA from baseline to day 11 were observed for all TAF dose groups compared with placebo (P < 0.01), with a median decrease of 1.08-1.73 log10 copies per milliliter, including a dose-response relationship for viral load decrease up to 25 mg. At steady state, 8, 25, and 40 mg TAF yielded mean TFV plasma exposures [area under the plasma concentration-time curve (AUCtau)] of 97%, 86%, and 79% lower, respectively, as compared with the TFV exposures observed with 300 mg TDF. For 25 and 40 mg TAF, the mean intracellular peripheral blood mononuclear cell tenofovir diphosphate AUCtau was ∼7-fold and ∼25-fold higher, relative to 300 mg TDF. Compared with 300 mg TDF, TAF demonstrated more potent antiviral activity, higher peripheral blood mononuclear cell intracellular tenofovir diphosphate levels, and lower plasma TFV exposures, at approximately 1/10th of the dose. This may translate into greater antiviral efficacy, a higher barrier to resistance, and an improved safety profile relative to TDF, supporting further investigation of TAF dosed once daily in HIV-infected patients.